Through the Gate: The implementation, management and delivery of resettlement service provision for short-term prisoners: - Millings, Matthew (Probation journal, 2018)
This paper draws upon research documenting the implementation, management and delivery of Through the Gate service provision in one case study area across an 18-month period. In referring to interviews and focus groups with professionals, male prisoners, and the families of these men, the paper provides a critical examination of the practice implications of administering Through the Gate provision in a resettlement prison. In doing so we reflect upon the changes in organisational structures, the evolution of occupational culture(s), and on the impact on multi-agency partnership working practice evident within this Transforming Rehabilitation led period of transitional change.